2017
DOI: 10.1021/acs.nanolett.7b01253
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nonradiative Defects and Environmental Oxygen on Exciton Recombination Processes in CsPbBr3 Perovskite Nanocrystals

Abstract: Lead halide perovskite nanocrystals (NCs) are emerging as optically active materials for solution-processed optoelectronic devices. Despite the technological relevance of tracing rational guidelines for optimizing their performances and stability beyond their intrinsic resilience to structural imperfections, no in-depth study of the role of selective carrier trapping and environmental conditions on their exciton dynamics has been reported to date. Here we conduct spectro-electrochemical (SEC) experiments, side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
116
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(135 citation statements)
references
References 106 publications
12
116
0
1
Order By: Relevance
“…Despite this, the effects of the environment on the optical properties of lead halide perovskites NCs have been surprisingly poorly investigated to date, with only few experiments on CsPbBr 3 nanocubes grown by hot-injection method, curiously finding contradictory results. In particular, the PL intensity in air has been reported to be lower than in vacuum [3,28], or not affected by the environment [27]. These results are different from the ones on single crystals, bulk polycrystalline thin films, and even nanosheets and nanowires [3], all showing a PL intensity enhancement in air.…”
Section: Introductionmentioning
confidence: 83%
“…Despite this, the effects of the environment on the optical properties of lead halide perovskites NCs have been surprisingly poorly investigated to date, with only few experiments on CsPbBr 3 nanocubes grown by hot-injection method, curiously finding contradictory results. In particular, the PL intensity in air has been reported to be lower than in vacuum [3,28], or not affected by the environment [27]. These results are different from the ones on single crystals, bulk polycrystalline thin films, and even nanosheets and nanowires [3], all showing a PL intensity enhancement in air.…”
Section: Introductionmentioning
confidence: 83%
“…. Moreover, the luminescence features can even be affected by the ambient atmosphere and this phenomenon was also assigned to surface defects . When preparing CsPbBr 3 QDs or films, equal moles of CsBr and PbBr 2 do not result in the highest QY and the QY values often vary in a wide range, depending on the mole ratio .…”
Section: Introductionmentioning
confidence: 99%
“…O 2 was then used as a molecular probe to compare and contrast the ability of the proposed ALD modes to grow gas diffusion barriers. Recent reports have demonstrated reduction in the PL of CsPbBr 3 NCs in the presence of molecular O 2 . The authors have suggested that this behavior is due to the interaction of O 2 with the NC surface.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we optimize the above‐mentioned ALD protection scheme for CsPbBr 3 NC films by using O 2 as a molecular diffusion probe to assess the uniformity of the encapsulating AlO x layer. The O 2 quenches the PL by extracting photogenerated charges . The better the gas barrier properties of ALD layer are, the less quenching is expected when the CsPbBr 3 /AlO x nanocomposites are exposed to an O 2 ‐rich atmosphere .…”
Section: Introductionmentioning
confidence: 99%